Heme oxygenase is not involved in the anti-proliferative effects of statins on pancreatic cancer cells - Vanova, K; Boukalova, S; Gbelcova, H; Muchova, L; Neuzil, J; Gurlich, R; Ruml, T; Vitek, L (BMC cancer, 2016)
BACKGROUND: Pancreatic cancer is recognized as one of the most fatal tumors due to its aggressiveness and resistance to therapy. Statins were previously shown to inhibit the proliferation of cancer cells via various signaling pathways. In healthy tissues, statins activate the heme oxygenase pathway, nevertheless the role of heme oxygenase in pancreatic cancer is still controversial. The aim of this study was to evaluate, whether anti-proliferative effects of statins in pancreatic cancer cells are mediated via the heme oxygenase pathway. METHODS: In vitro effects of various statins and hemin, a heme oxygenase inducer, on cell proliferation were evaluated in PA-TU-8902, MiaPaCa-2 and BxPC-3 human pancreatic cancer cell lines. The effect of statins on heme oxygenase activity was assessed and heme oxygenase-silenced cells were used for pancreatic cancer cell proliferation studies. Cell death rate and reactive oxygen species production were measured in PA-TU-8902 cells, followed by evaluation of the effect of cerivastatin on GFP-K-Ras trafficking and expression of markers of invasiveness, osteopontin (SPP1) and SOX2. RESULTS: While simvastatin and cerivastatin displayed major anti-proliferative properties in all cell lines tested, pravastatin did not affect the cell growth at all. Strong anti-proliferative effect was observed also for hemin. Co-treatment of cerivastatin and hemin increased anti-proliferative potential of these agents, via increased production of reactive oxygen species and cell death compared to individual treatment. Heme oxygenase silencing did not prevent pancreatic cancer cells from the tumor-suppressive effect of cerivastatin or hemin. Cerivastatin, but not pravastatin, protected Ras protein from trafficking to the cell membrane and significantly reduced expressions of SPP1 (p < 0.05) and SOX2 (p < 0.01). CONCLUSIONS: Anti-proliferative effects of statins and hemin on human pancreatic cancer cell lines do not seem to be related to the heme oxygenase pathway. While hemin triggers reactive oxygen species-induced cell death, cerivastatin targets Ras protein trafficking and affects markers of invasiveness.
Keywords: RNA, Messenger; Pancreatic cancer; kvantitativní polymerázová řetězová reakce; hemoxygenasa-1; Cell Proliferation; reaktivní formy kyslíku; pankreas; western blotting; Hydroxymethylglutaryl-CoA Reductase Inhibitors; signální transdukce; statiny; Ras proteiny; Pancreas; polymerázová řetězová reakce s reverzní transkripcí; Real-Time Polymerase Chain Reaction; Signal Transduction; Pancreatic Neoplasms; Cell Movement; Statins; Reactive Oxygen Species; Blotting, Western; lidé; Humans; nádory slinivky břišní; pohyb buněk; nádorové buňky kultivované; Reverse Transcriptase Polymerase Chain Reaction; apoptóza; Heme oxygenase; proliferace buněk; Tumor Cells, Cultured; Heme; ras Proteins; Heme Oxygenase-1; messenger RNA; Apoptosis